Travel intention determinants during COVID-19: The role of trust in government performance - Huan Minh Nguyen; Phuc Hung Nguyen; Duong Thien Tam (Journal of Innovation & Knowledge (JIK), 2023)
The Coronavirus disease 2019 (COVID-19) has compelled tourism experts to devise efficient ways to attract visitors. Based on the theory of planned behavior (TPB) model, this study created a comprehensive model of residents' trust in government performance, perceived risk, and travel intention. The model was tested on 469 Vietnamese residents using confirmatory factor analysis and structural equation modeling. The findings reveal that perceived risk negatively impacts attitudes toward travel, perceived behavioral control, and subjective norms, while trust in government performance positively impacts these categories. Furthermore, attitude toward travel, perceived behavioral control, and subjective norms positively influence a tourist's travel intention. This study offers theoretical and practical insights into how to build safe tourism practices and design appropriate COVID-19 recovery programs in the tourism industry.
Keywords: 650; COVID-19; Perceived risks; Theory of the planned behavior; Travel intention; Trust in government performance; Vietnam